Shareware Explosion!. - Miller, Jack
Sure, Adobe, Macromedia, Microsoft and other big-name developers create the bulk of the software we use everyday-but an army of independent code-crafters are turning out more top-notch shareware and freeware apps than ever before. Here are 100 of the best.